Application of Critical Chain Project Management (CCPM) in Overcoming Resource Inefficiency in Multi-Project Management of Drinking Water Treatment System (SPAM) Development in The National Capital City (IKN) - Habib Amrulloh; Kamalul Asfiyak; Rian Ramadhan; Ina Agustini Murwan (LP2M IAIN Palopo, 2026)
The development of the Drinking Water Supply System (SPAM) in Indonesia’s new capital city (IKN) faces critical challenges of resource inefficiency in multi-project management. The main issues identified include fragmented planning and execution, weak cross-project coordination, manual information systems, and the absence of centralized command in resource allocation. This study aims to analyze the root causes of these inefficiencies and formulate solutions through the application of Critical Chain Project Management (CCPM) integrated with the Six Sigma DMAIC methodology. The research employed a mixed-method approach combining qualitative and quantitative analysis, including Pareto, Fishbone Diagram, Current Reality Tree (CRT), and the Theory of Constraints (TOC) Thinking Process. The Define and Measure phases identified planning fragmentation and poor coordination as dominant problems. The Analyze phase mapped root causes using CRT, while the Improve phase developed strategies based on the SWOT–TOWS framework, emphasizing the establishment of a digital-based Resource Control Center (RCC), implementation of CCPM buffer management, and digital transformation toward real-time project information systems. The Control phase ensured sustainability through buffer monitoring, periodic audits, and cross-project KPI dashboards. The results show that the CCPM–DMAIC integration enhances resource efficiency, minimizes idle time and delays, and promotes collaborative culture among stakeholders. The WO strategy proved most relevant, leveraging IKN’s development momentum and digitalization opportunities to address coordination weaknesses. Overall, CCPM–DMAIC provides an effective model for achieving efficiency, collaboration, and sustainability in national infrastructure projects.